Wealth shocks, unemployment shocks and consumption in the wake of the Great Recession - Dimitris Christelis; Dimitris Georgarakos; Tullio Jappelli (European Central Bank (ECB), 2015)
Data from the 2009 Internet Survey of the Health and Retirement Study show that many U.S. households experienced large capital losses in housing and financial wealth, and that 5% of respondents lost their job during the Great Recession. As a consequence of these shocks, many households reduced substantially their expenditures. For every 10% loss in housing and financial wealth, the estimated drop in household expenditure is about 0.56% and 0.9%, respectively. In addition, those who became unemployed reduced spending by 10%. We also distinguish the effect of perceived transitory and permanent wealth shocks, splitting the sample between households who think that the stock market is likely to recover in a year's time, and those who do not. In line with the predictions of standard models of intertemporal choice, we find that the latter group adjusted much more than the former its spending in response to financial wealth shocks.
Keywords: E21; D91; 330; Consumption; Great Recession; Unemployment; Wealth Shocks; Wirtschaftskrise; Vermögenseffekt; Privater Konsum; Arbeitslosigkeit; USA